Correlation of mitosis obtained by using 1% crystal violet stain with Ki67LI in histological grades of oral squamous cell carcinoma - Priyanka Kadoo; Rishikesh Dandekar; Meena Kulkarni; Aarti Mahajan; Ramniwas Kumawat; Neeta Parate (Journal of Oral Biology and Craniofacial Research)
Aim: The purpose of this study was to use a simple, cost-effective technique for studying mitosis in various grades of oral squamous cell carcinoma (OSCC) using 1% Crystal-violet stain and to correlate mitotic frequency index (MFI) obtained by it with Ki67 labeling index (Ki67LI) so as to validate its usefulness as a selective stain for evaluating proliferation. Materials and Methods: The invasive front grading score (IFG Score) was recorded in 40 patients of OSCC. Mitotic figures were assessed in hematoxylin and eosin (H and E) stained section as well as in 1% crystal-violet stained section using MFI (MFI = Mitosis/total number of cell counted X100). Comparison between MFI obtained by 1% crystal violet stain and H and E stain was done. Ki67LI was assessed using Ki67 immunohistochemical (IHC) marker. Correlation between Ki67LI and MFI obtained by using 1% crystal-violet stain was performed. Results: There was statistically significant increase in MFI obtained by using 1% crystal-violet stain compared to routine H and E stain. Statistically significant positive correlation was observed between Ki67LI and mitosis in well and moderately differentiated OSCC. Positive correlation was also observed in poorly differentiated OSCC, but it was not statistically significant. Both mean MFI and mean Ki67LI significantly increased from grade I to grade II to grade III OSCC. Conclusion: 1% crystal violet stain provides a definite advantage over the H and E stained sections. Thus crystal violet stain is easy and cost effective to evaluate proliferation when compared with expensive proliferative IHC marker.